CPA Examination: Theory of Accounts. - Zlatkovich, Charles T. (The Accounting Review, 1965)
Abstract The article presents the theory of accounts portion of the May 14, 1965, Uniform Certified Public Accountants Examination by the Board of Examiners of the American Institute of Certified Public Accountants (CPA). Answers should be submitted by well-prepared candidates writing within the time limits prescribed. They do not necessarily include all elements for which credit might be given by the Advisory Grading Service of the American Institute of CPAs or by the various state accountancy boards charged with the responsibility of issuing CPA certificates. The first problem presents a graph describing the behavior of the cost, expense, income or valuation amount that would appear on a series of annual financial statements for each of the independent situations. All policy decisions and events that caused changes in the behavior patterns of the charted amounts took place in the middle of the time span portrayed in the graphs. The vertical axes of the graphs represent the annual dollar amount of cost, expense income or valuation, as the case may be, and the horizontal axes represent the passage of time. The axes intersect at zero.